Environmental Health Indicators Affect On The Acheivement Of Community Health Development Index In Tanjung Jabung Timur District - Andy Amir; Dwi Noerjoedianto; Andi Subandi (International Journal of Health Engineering and Technology, 2022)
The Public Health Development Index (IPKM) is composite indicator that describe the progress of health development in a district. Enviromental health is one of the indicator contained in the IPKM. There are 2 sub-indicator for environmental health, access to clean water and access to sanitasion. This research was conducted in Tanjung Jabung Timur regency with the aim of knowing the description of IPKM achivements on environmental health indicator in 2016-2018. Methodology this was quantitative research. This study was conducted 5 months starting from May to October 2021. Data analyzed used public health development index formula that has been determined by calculating weights for each indicator and then used minimum and maximum standars values. This study found that the sub-index value of the group from 2016-2018 continued to increase. In 2016 amounted to 0.111411387, in 2017 amounted to 0.363059484, and in 2018 amounted to 0,696495001. The results of this study indicate that for 3 consecutive years the environmental health conditions have continued to improve towards a better direction, both in terms of access to clean water and access to sanitation. However, it still to improvements access to clean water and access to healthy sanitation so that it evenly distributed for all communities in Tanjung Jabung Timur Regency.